2017
DOI: 10.1111/imj.13571
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the practice of palliative care doctors: what driving advice do they give patients with advanced disease?

Abstract: This is the first survey investigating the practice of Australian doctors in assessing fitness to drive of patients with advanced disease. The survey found wide variability in practice and substantial discordance with current driving guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To our knowledge, this is the first systematic review evaluating driving in patients with brain tumours and incidence of MVC. To date, most published research has focused on clinician attitudes and practices towards driving guidelines [ 15 19 ]. Our review demonstrates a paucity of real-world data concerning MVC incidence amongst these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first systematic review evaluating driving in patients with brain tumours and incidence of MVC. To date, most published research has focused on clinician attitudes and practices towards driving guidelines [ 15 19 ]. Our review demonstrates a paucity of real-world data concerning MVC incidence amongst these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study evaluating driving recommendations among healthcare professionals, found that only 56% discussed driving recommendations with patients and only 9.3% could reliably determine fitness to drive [ 18 ] . In a survey of Australian and New Zealand palliative care clinicians, only 27% reported patients with brain tumours to driving authorities [ 19 ] . Similarly, a Canadian study demonstrated low mandatory reporting rates with poor documentation of medical discussions regarding safe driving [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our sample size was too small to conduct statistical analyses on the implications of histological subtype on cognitive testing and driving performance. Other research in the field has shown that advanced intracranial disease is not only associated with increased tumor burden, increased utilization of adjuvant therapies such as radiation therapy, poorer cognition, and lower capacity for reasoning/decision-making, but also increased utilization of complex narcotic regimens 20 , 21 . The use of a new narcotic is associated with increased on-road collisions and traffic violations and for that reason amongst several others, many palliative care doctors would consider this subset of the neuro-oncological population at greater risk of unsafe driving 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, clinicians advise patients not to drive immediately after taking opioids. [45] There is a need for further research to understand if patients taking regular, low-dose, sustained-release morphine are able to drive safely given the different pharmacokinetic profile they have to immediate-release oral morphine solutions. [46] The relation between breathlessness and driving performance whist on opioids must also be explored as current legal morphine limits for driving (where imposed) are far higher than the doses used in this study.…”
Section: Main Findingsmentioning
confidence: 99%